2015
DOI: 10.1186/s12886-015-0086-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of scleral cross-linking using genipin on the process of form-deprivation myopia in the guinea pig: a randomized controlled experimental study

Abstract: BackgroundScleral cross-linking (CXL) is a novel attempt to slow down the axial elongation process in animal eyes. As a natural CXL reagent, genipin would be also effective for the prevention of myopia process. Thus, the present study was designed to evaluate the effects of scleral cross-linking using genipin on the form-deprivation (FD) myopia process of guinea pigs.MethodsTwenty-seven 3-week-old pigmented guinea pigs were randomly divided into three groups. Group A (n = 8) is the untreated control group. Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 26 publications
1
43
0
Order By: Relevance
“…79 Wollensak 10 has described previously the use of a sT injection using glyceraldehyde (a chemical crosslinking agent similar in concept to the FARs described in this study) to stiffen the rabbit sclera 10 and genipin has been shown to limit axial length in FD guinea pigs. 11,12 These investigators have demonstrated an advantage of using a soluble chemical agent over the photochemical (CXL) technique. Making an injection into sT space is much simpler than carrying out the photochemical procedure, which requires a surgical procedure to access the posterior sclera with a UV light source.…”
mentioning
confidence: 99%
“…79 Wollensak 10 has described previously the use of a sT injection using glyceraldehyde (a chemical crosslinking agent similar in concept to the FARs described in this study) to stiffen the rabbit sclera 10 and genipin has been shown to limit axial length in FD guinea pigs. 11,12 These investigators have demonstrated an advantage of using a soluble chemical agent over the photochemical (CXL) technique. Making an injection into sT space is much simpler than carrying out the photochemical procedure, which requires a surgical procedure to access the posterior sclera with a UV light source.…”
mentioning
confidence: 99%
“…Our results support this idea as SXL using genipin strengthened the myopic scleras by inhibiting inelastic deformations due to cyclic loading. Wang and Corpuz have successfully used subconjunctival injection of 0.5% (22.1 m m ) genipin to slow form‐deprivation myopia in guinea pigs. We have used a much lower concentration of 0.25 m m in this study suggesting that a low but sustained delivery (24 h in this study) of genipin to the sclera may lead to significant biomechanical strengthening.…”
Section: Discussionmentioning
confidence: 99%
“…It is a naturally occurring organic compound derived from the fruit of the gardenia plant ( Gardenia jasminoides ) . Genipin has been shown to alter the scleral material properties of porcine sclera and to slow myopia progression in guinea pigs . Campbell et al .…”
Section: Introductionmentioning
confidence: 99%
“…119,120 UV-A use with scleral CXL has been associated with decreased dark-adapted ERG amplitudes up to 3 months posttreatment, with apoptotic cells and ultrastructural changes in retina layers also found. 121 111,118,119,[122][123][124][125][126][127][128][129][130] Glyceraldehyde is a non-light-activated chemical shown to increase scleral rigidity, but has ill effects on the neighboring cornea and muscles. 120 Alternatively, topical beta-nitroalcohols (or ''BNAs,'' commonly found in antibiotics and shampoos) and formaldehyde releasers (or ''FARs,'' which are preservatives found in cosmetics, body wash, and ophthalmic solutions; e.g., BLU Gel A multidose artificial tears, SOOFT italia [Montegiorgio FM, Italy]) effectively crosslink corneal and scleral collagen in vitro, and have very good safety profiles (Hoang Q, et al IOVS 2013;54:ARVO E-Abstract 136).…”
Section: Solution 3: Advanced Stage Disease Interventions: Current Anmentioning
confidence: 99%